AN ANALYSIS OF STANDARD ENGLISH AND GENERAL AMERICAN VARIETIES IN TEACHING SPEAKING OF FKIP UIR-PEKANBARU - Estika Satriani; Afrizal Afrizal; Arimuliani Ahmad (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
Standard English and General American are part of varieties of English that are used and learned in education world. Formerly only Standard English had been taught, but lcently General American has been taWht as well. Nowadays, both varieties of General American and Standard English are found in university "of Indonesia. Based on this phenomena, the writers think, some problem may occur when deciding which variety to teach in the classroom. The purpose of this study is to finiout the aititudes of eight EFL lecturers of English toward differert varieties of English, namely Standard English and General Amirican. Likewise, the researchers want to find out ifthese varieties are reflected in their classroom teaching as well as what their views are on student's use of the variety of English in question. The study was carried out in Islamic University of Riau Pekanbaru. The participants were inteiviewed by "alternative" and "open ended', questions. The results of this study showed that the Standard English variety was most frequently used among English lecturers at Islamic University of Riau when teaching speaking English than the General American variety. Furthermore, the lecturers' 'formal', varieties illustrated that standard english was considered as "educated", "polite","better constnrction of sentence", etcetera. General American was described as being "friendly", "simple", "commonly used", "young approached" and so on.